2008
DOI: 10.1016/j.cej.2007.09.004
|View full text |Cite
|
Sign up to set email alerts
|

Modeling of a bacterial and fungal biofilter applied to toluene abatement: Kinetic parameters estimation and model validation

Abstract: Biofiltration has been established as a promising alternative to conventional air pollution control technologies. However, gas biofilters modeling has been less developed than experimental research due to the complexity of describing the fundamental processes and the lack of globally accepted\ud physical, chemical and biological parameters. In addition, biofiltration modeling based on degradation activity of fungi has been rarely considered.\ud For this reason, in thiswork, a dynamic model describing toluene a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
54
0
7

Year Published

2008
2008
2020
2020

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 80 publications
(61 citation statements)
references
References 40 publications
0
54
0
7
Order By: Relevance
“…According to Dorado et al (2008) µ max /Y x/o may be lumped in a coefficient q max (mg DO·g VSS -1 ·s -1 ).…”
Section: Biofilm Modelingmentioning
confidence: 99%
“…According to Dorado et al (2008) µ max /Y x/o may be lumped in a coefficient q max (mg DO·g VSS -1 ·s -1 ).…”
Section: Biofilm Modelingmentioning
confidence: 99%
“…Since toluene is an organic material much less soluble in water, its concentration after this layer varied not as much as that of acetone. Removal efficiency of pollutants from cleaned air depends on gas residence time in biofilters (AlvarezHornos et al, 2007;Dorado et al 2008Dorado et al , 2010Dorado et al , 2012aGracy et al, 2006;Hwang and Tang, 1997;Jeong at al., 2006;Qi, 2005;Yoon and Park, 2002;Zilli et al, 2001). The longer is the empty bed residence time (EBRT) of polluted gas the higher removal efficiency can be observed.…”
Section: Cpeczasopismapanpl; Degruytercom/view/j/cpementioning
confidence: 99%
“…In the recent papers of Dorado et al (2008Dorado et al ( , 2010Dorado et al ( , 2012a the authors provided more information on the performance of biofilters packed with different hybrid packing material covered by a thin layer of compost and inoculated with activated sludge from a municipal WWTP and applied them to purify air containing toluene vapour. Dorado et al (2012a) found that biomass accumulation in a biofilter was enhanced by the high toluene load, particle size of the material, and its spatial distribution in the bed enabled to collect information on biomass growth.…”
Section: Introductionmentioning
confidence: 99%
“…Thus, different mathematical and statistical models have been proposed in the literature. [17][18][19][20][21] Nevertheless, microbial growth with degrading activity is a wholly undetermined key parameter that governs biofilter "success." The support material itself can supply the biomass responsible for degradation.…”
Section: Introductionmentioning
confidence: 99%